The scientific method in forensic science: a Canadian handbook - Illes, Mike (Canadian Scholars, 2020)
"This handbook provides an experience-based learning opportunity to understand the scientific method and evidence-based analysis as they relate to forensic science casework in Canada and abroad. Underscoring the importance of these concepts, the handbook features real-world case examples and court testimonies that depict how science rigor has and has not been incorporated into practice and the consequences in the latter case. The authors explore the paradigm shift in forensic science (examining various reports that highlighted issues within the discipline, such as insufficient scholarly peer reviewed research, lack of scientific training, lack of governance); skills like reviewing a journal article and conducting a literature review; and scientific concepts and scientific reasoning. They also untangle the complexities of ethics and bias, research design, critical thinking, and best practices for communication in forensic science."--